TEKNIK DAN INSTRUMEN PENILAIAN RANAH KOGNITIF TEKNIK NON TES DAN PENERAPANNYA DALAM PENDIDIKAN ANAK USIA DINI - Istifadah, Shovi Yatul (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
The cognitive domain deals with the process of evaluating individual thinking abilities or problem solving abilities. There are 9 characteristics of cognitive development, which can understand the concept of opposite meanings such as empty-full, light-heavy, top-bottom, and so on. Can match geometric shapes (circles, squares and triangles) with real objects or through visualization of images, Can stack blocks or rings according to their size in sequence. Can group objects that have the same color, shape, and size. Can mention pairs of objects, able to understand cause and effect. Can arrange daily activities and show when each activity is carried out. Retell 3 main ideas from a story. Recognize and read writing through images that are often seen at home or at school. Recognize and mention numbers 1-10. This cognitive domain assessment technique uses rating scales, check lists and anecdocate notes.